The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

“Me Too”: Epistemic Injustice and the Struggle for Recognition - Jackson, Debra L. (Feminist Philosophy Quarterly, 2018)
Congdon (2017), Giladi (2018), and McConkey (2004) challenge feminist epistemologists and recognition theorists to come together to analyze epistemic injustice. I take up this challenge by highlighting the failure of recognition in cases of testimonial and hermeneutical injustice experienced by victims of sexual harassment and sexual assault. I offer the #MeToo movement as a case study to demonstrate how the process of mutual recognition makes visible and helps overcome the epistemic injustice suffered by victims of sexual harassment and sexual assault. I argue that in declaring “me too,” the epistemic subject emerges in the context of a polyphonic symphony of victims claiming their status as agents who are able to make sense of their own social experiences and able to convey their knowledge to others.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; harcèlement sexuel; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; philosophie féministe; périodes historiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éthique

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Race, racisme, discriminations: anthologie de textes fondamentaux - Bessone, Magali; Sabbagh, Daniel (Avocat du diable, 2015)
« La race n'est-elle qu'une chimère - une fiction collective aux effets pernicieux - ou est-elle un concept nécessaire à l'analyse et à l'éradication éventuelle du racisme et de ses conséquences? Cette catégorie ambiguë relève-t-elle de la biologie ou bien renvoie-t-elle à une réalité de nature socio-politique? Le racisme est-il d'abord un attribut des individus ou des institutions - un état mental fait de croyances et d'affects ou un système social? Toute discrimination raciale est-elle inévitablement raciste? Est-elle immorale et injuste même dans les cas où elle ne serait pas entièrement irrationnelle? Enfin, la discrimination positive est-elle justifiable? Telles sont quelques-unes des questions abordées dans ce recueil, qui propose une introduction au champ d'investigation que la race, le racisme et les discriminations constituent pour la philosophie - ici envisagée dans son articulation avec les sciences sociales. Il réunit dix textes majeurs, presque tous inédits en français. »
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; antiracisme; approches et analyses; cours; discipline; discriminations; europe; occident; phi4336; philosophie; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences